Pathways From Dependency and Neglect to Delinquency in a Mid-South County in the United States, 1984-1985 and 2000-2001 - Coleman-Davis, Veronica F. ([Verlag nicht ermittelbar], 2010)
The purpose of this study was to examine two sets of children -- those alleged dependent and neglected and those alleged delinquent -- in order to better understand the influence of maltreatment on delinquent conduct. Data were collected from official court records. The first group of children was selected from the dependency and neglected cases filed with the Juvenile Court in 1984 and 1985. The 1984-1985 Non-Pooled Dependency and Neglect Cohort Data (Part 1) contains a total of 1,062 cases, representing 1,062 alleged dependent and neglected children and their siblings. The 1984-1985 Pooled Dependency and Neglect Cohort Data (Part 3) includes 4,474 cases which correspond to up to 20 complaints for each of the 1,062 alleged dependent and neglected children. The second group was selected from delinquency petitions of children 16 and 17 years old filed in the years 2000 and 2001. The 2000-2001 Non-Pooled Delinquency Cohort Data (Part 2) contains a total of 549 cases, representing 549 delinquent children. The 2000-2001 Pooled Delinquency Cohort Data (Part 4) includes 2,076 cases which correspond to up to 20 complaints for each of the 549 delinquent children. Part 1 contains a total of 11 and Part 2 contains a total of 10 demographics and summary count information variables. Part 3 and Part 4 contain a total of 68 and 58 variables, respectively, including demographics and information on delinquent charges, complaints of maltreatment, placements, and dispositions for each child.